Powiązania kursu walutowego i wymiany handlowej Polski: Relationship between exchange rate and Polish trade - Przekota, Grzegorz; Lisowska, Agnieszka (Management and Administration Journal, 2021)
The study relate the relationship between the exchange rate and the level of Polishtrade. Analyzed monthly data for the period January 2000 - December 2011. The researchfound that the relationship between the exchange rate and the level of trade is not based ona simple correlation. However, it was found that in the formation of trade is the dominant roleof the dollar over the euro. In addition, causality the trade - the exchange rate is bilateral.